VIDEO DEVELOPMENT AS SUPPORTING LEARNING MEDIA FOR STUDENTS IN CULTURE OF INFORMATION AND COMMUNICATION TECHNOLOGY IN PASCASARJANA UNIVERSITAS NEGERI JAKARTA - Suyitno Muslim; Aniesa Puspa Arum (Peneliti.net, 2019)
This study aims to: (1) produce a learning video for the subject which is appropriate to be applied as learning media for Pascasarjana student teknologi pendidikan, and (2) investigate the approprioateness of the learning video at pascasarjana UNJ in order to be appropriate to be applied as learning media. The development of the learning video pascasarjana UNJ employed the Researcg & Development method by Allesi & Trollip, consisting of three development steps, i.e.: (1) planning: determining needs and objectives, colleting resources, and producing ideas; (2) design: making the flowchart and storyboard and preparing the script; and (3) development: producing the video and audio, programming the materials, preparing the supporting components, evaluating, and revising. The result of the development research was a learning video was assesses by a media expert, a materials expert, and students as users of the media. On the whole, the tryouts showed good results in the appropriate category with the following details. (1) from the materials expert the mean score was 5.55, which was in the appropriate category. (2) from the media expert the mean score was 3.5, which was in the appropriate category. (3) from the small-scale tryout involving students the mean score was 3.5, which was in the appropriate category. (4) from the large-scale tryout involving students the mean score was 3.19, which was in the appropriate cetagory. Based on the media appropriateness assessement, it can be conclude thet the learning video is sppropriate to be used as learning media at pascasarjana UNJ.